2001
DOI: 10.1053/jhep.2001.25086
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Tight Junctions Differ Between Primary Biliary Cirrhosis and Primary Sclerosing Cholangitis

Abstract: Tight junctions (TJ) of biliary epithelial cells (BEC) and hepatocytes prevent bile regurgitation from the biliary tract. Alterations in these TJs may participate in chronic cholestatic liver diseases such as primary biliary cirrhosis (PBC) and primary sclerosing cholangitis (PSC). We examined the localization of 2 TJ proteins, ZO-1 and 7H6, in these diseases. Frozen sections from livers of PBC, PSC, extrahepatic cholestasis (Ex-C), and hepatitis C-associated cirrhosis (LC-C), as well as histologically normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 38 publications
2
81
0
Order By: Relevance
“…8 In intrahepatic cholestasis, alterations of tight and gap junctional functions are frequently observed, which results in impaired intercellular communication and leaky canalicular structures. [9][10][11] Although the changes in gap junctions and TJs had been considered independent of each other, recent findings have shown that ZO-1 and occludin bind to connexins, which raises the possibility of either coordinate or reciprocal regulation of macromolecular complexes containing gap and TJ proteins. 24 The effects of HCV on gap junctions are currently being studied in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In intrahepatic cholestasis, alterations of tight and gap junctional functions are frequently observed, which results in impaired intercellular communication and leaky canalicular structures. [9][10][11] Although the changes in gap junctions and TJs had been considered independent of each other, recent findings have shown that ZO-1 and occludin bind to connexins, which raises the possibility of either coordinate or reciprocal regulation of macromolecular complexes containing gap and TJ proteins. 24 The effects of HCV on gap junctions are currently being studied in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Cholestatic hepatocytes show alterations of TJ functions, resulting in a deteriorated "barrier" function. [9][10][11] Recurrence of HCV infection after liver orthotopic transplantation is commonly associated with a rapid progression of a cholestatic form of hepatitis and leads to accelerated graft failure and death. 12 On recurrence, serum concentrations of HCV RNA may reach 10 to 20 times pretransplantation values, and high HCV protein expression in the transplanted liver is associated with the development of acute and chronic hepatitis.…”
mentioning
confidence: 99%
“…Its multifarious pharmacological effects such as bile excretion-accelerating effect and liver cell-protecting effect are well known (13,14). Recently, the anti-apoptotic effect of UDCA has also been elucidated (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that inhibition of the Na ϩ /H ϩ exchanger is associated with a reduction in cholangiocyte functional activity 47 and ductal bile flow. 48 Therefore, cariporide could exert its positive effects in several ways: (1) by reducing bile flow, thus reducing the intraductal pressure that is commonly associated with an alteration of paracellular permeability, toxic compound spillover, and hepatocyte damage 49 ; (2) by reducing fibrosis and consequently intraductal pressure; and (3) by preventing the ductular reaction induced by BDL. In fact, ductular reaction is considered to be protective in a cholestatic condition, but it resolves in parenchymal damage when the obstacle to bile flow remains.…”
Section: Discussionmentioning
confidence: 99%